PENENTUAN WAKTU IB TANPA SINKRONISASI ESTRUS PERIODE POSTPARTUM BERDASARKAN PROFIL HORMON ESTROGEN DAN LUTEINIZING HORMONE (LH) PADA KAMBING LOKAL - Mirajuddin, Mirajuddin (AgriSains, 2012)
Research on â€œdetermination of AI timewithout estrus synchronization in post partum period beased on estrogen hormone profile and LH in local goat ", is part of the National Strategic Research Grant, which is funded by the University Tadulako in Fiscal Year 2010. The research was done at the Laboratory of Physiology and Reproduction, Faculty of Animal Science, University of Gajah Mada (UGM), Integrated Research and Testing LaboratoryÂ  UGM, Laboratory of Obsterics, Department ofÂ  Animal Reproductive Medicine, University of Airlangga,Â  group of Goat farmers in the city of Palu. This study aimed to find solutions to the failure of the AI implementation Central Sulawesi, due to the limitations of frozen sperm, liquid Nitrogen, and the expensiveness of estrus synchronization hormon. Post partum local goatwas used as experimental animal. Blood was taken forÂ  analysisÂ  estrogen and LH hormonesÂ  (immunometric assay) in one estrous cycle, namely in 36 -55 days after giving birth. Implementation of the AI (without estru synchronization) was based on the time and the highest concentration of estrogen (1000 Ïg / ml, as treatment 1), the concentration of LH surge (160 Î·g / ml: treatment 2), and on the first day after the LH surge (as treatment 3), while the implementation of the AI with estrus synchronization was as the control (treatment 0). The AI implementation was done by using liquid sperm of Etawah cros-bred goatÂ  that were prepared with 2.5% tannin (leucocephala) supplementation per ml sperm. Conception rate (conception rate: CR) of AI was calculated based on the percentage of non pregnant femalesd (nonreturn Rate: NRR) of total females artificially inseminated, where the treatment 1 was 20%, 73.3% (treatment 2), 60% (treatment 3), and Control ofÂ  86.6%.Key words: Estrogen hormon and LH, Postpartum, AI, estrus synchronization, and local goat.